The Effect of Competition Intensity and Competition Type on the Use of Customer Satisfaction Measures in Executive Annual Bonus Contracts - Chen, Clara Xiaoling; Matsumura, Ella Mae; Shin, Jae Yong; Wu, Steve Yu-Ching (The Accounting Review, 2015)
ABSTRACT This paper empirically examines the interactive effect of competition intensity and competition type on the use of customer satisfaction measures in executives' annual bonus contracts. Specifically, we predict a stronger association between competition intensity in an industry and the use of customer satisfaction measures in executives' annual bonus contracts when the competition is non-price-based than when the competition is price-based. Using hand-collected data from Standard & Poor's (S&P) 1500 firms' disclosures of the use of customer satisfaction measures in executive bonus contracts in 2006 and 2010 proxy statements, we find results consistent with our prediction. Our results are robust to alternative measures of competition type and competition intensity. We also find similar results when we use the weight on customer satisfaction measures in executive bonus contracts as the dependent variable. Our study extends the literature on the effect of competition on the design of managerial incentives by distinguishing between competition intensity and competition type, and providing the first large-sample empirical evidence on the joint effect of these two dimensions of competition on the incentive use of an important nonfinancial performance measure. Data Availability: Data used in this study are obtained from publicly available sources.